2022
DOI: 10.4103/abr.abr_261_21
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Obesity and Serum Vitamin D Levels with Sperm DNA Integrity, Sperm Quality, and Sperm Viability in Normozoospermia Men

Abstract: Background: Obesity, Vitamin D (VD) deficiency, and infertility are important ubiquitous issue; however, the association of obesity and serum VD levels with abnormal sperm is unclear and inconclusive. The current study investigated the correlation of obesity and serum VD levels with sperm DNA integrity and sperm parameters in normozoospermia men. Materials and Methods: Semen and blood samples from 64 men were divided into two groups: obese and nonobese men based on body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
2
1
Order By: Relevance
“…According to Abbasihormozi et al, high BMI was negatively correlated with sperm normal morphology, sperm motility, progressive motility, and sperm count [ 41 ]. Contrary to our results, Pooladi et al reported a negative correlation between BMI and sperm motility (overall or progressive) but not sperm morphology and count [ 42 ]. Analyzing the studies, we found that the possible reasons for the inconsistencies might be related to different designs of studies, different sample sizes, different cut-off points of body mass index in determining obesity, and different health statuses of participants (infertile and healthy) in different studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…According to Abbasihormozi et al, high BMI was negatively correlated with sperm normal morphology, sperm motility, progressive motility, and sperm count [ 41 ]. Contrary to our results, Pooladi et al reported a negative correlation between BMI and sperm motility (overall or progressive) but not sperm morphology and count [ 42 ]. Analyzing the studies, we found that the possible reasons for the inconsistencies might be related to different designs of studies, different sample sizes, different cut-off points of body mass index in determining obesity, and different health statuses of participants (infertile and healthy) in different studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Several recent studies with interesting results have been conducted since the aforementioned meta-analyses [39][40][41][42]. For example, in a cross-sectional study, Esmaeili et al found that BMI was negatively correlated with normal sperm morphology, sperm total motility, and progressive motility, but it had no effect on sperm volume and concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DNA integrity was higher in obese individuals than in non-obese individuals. 12 Research has found that the somatic or germ cells of the testes are able to compose and degrade vitamin D locally, while the systematic vitamin D metabolism does not seem to affect the effect. In addition, it is reported that the expression of VDR in the testis demonstrates that vitamin D may exert both autocrine and paracrine effects and, thereby, affect male infertility.…”
Section: Association Of Vitamin D Insufficiency and Male Infertilitymentioning
confidence: 99%